(untitled) (International Research in Economics and Finance, 2022)
With all these mergers and acquisitions, it is particularly important to consolidate and manage the number of vendors inherited or absorbed via these acquisitions. This is also an avenue to build strong relationships with their selected suppliers because working with fewer vendors helps to optimize their entire supply chain and improves efficiency across procurement, delivery, production, assets management, and customer satisfaction. Another benefit will come from increased discounts due to preferential, scale, and volume pricing not to mention cost reduction in the areas of their supply chain management. Some companies have production plants in Texas, Tennessee, Florida, Ohio, Indiana, China, Canada, Mexico, and India, and the main aim is to identify suppliers close to those plants and streamline their logistics and distribution cost. There is also a high level of l risk associated with this exercise, If the supply is interrupted for any re-organization will face lots of difficulties meeting up demand, the absence of healthy competition will diminish the ability to negotiate SLAs (Service Level Agreements), and pricing against a supplier competitor but the business goal is to: Invest in Innovations, research and develop new products to be able to remain competitive, this cannot be achieved without the optimization of Procurement, Sourcing and Vendor Management. Be able to automate Procurement and Sourcing operations to increase business dynamism. This consolidation will reduce costs and free up funds to achieve their broader business goal and a bloated suppliers portfolio scattered all over the world conceals a lot of opportunities to get more with less. There were lots of political issues uncovered and encountered during this project which was anticipated but was carefully managed. Companies should think ahead and move from strong market position, growth, and reaching critical customers to accelerating profitable growth. Push the organization from a push/OEM channels a to pull strategy a with focus on end users. Ensure their product offering moves from a specific specialized brand to global recognition. Strong technological know-how to become a true and trusted innovative leader. Move from presence in new markets to leader in all markets. It is also advisable for companies to consider Vertical Integration which is a different alternative to Supplier Consolidation, and conduct financial and regression analyses for better decision-making and recommendations that will give a very big boast to their bottom line. This integration will avoid any supply disruption and organizations will have full control of their supply chain. Since Suppliers are known to dictate terms, pricing, and availability of materials, with this Integration, costs will be reduced, and production slowdowns caused by negotiations and other internal tussles will be prevented. This does not go without some risks because there is always a huge capital investment to set this up, to buy the factories and, to ensure that the plant is running efficiently and effectively.